Klinik Penulisan Ilmiah Bagi Para Guru Berbasis PAR - Abdulloh Fuadi; Baiq Widia Nita Kasih (Universitas Islam Negeri Mataram, Indonesia, 2022)
The scientific paper writing training activity for teachers aims to improve growth mindsets regarding writing skills, provide exposure to the components of writing from the idea of ??seeking research to publications, improve the ability to write scientific papers based on participatory action research needs analysis among teachers.and school stakeholders, teachers can develop their self-efficacy and careers by writing, as well as producing drafts of scientific journal articles for each participant of the service program. The Scientific Writing Clinic for Teachers Based on Participatory Action Research consists of two main activities, namely offline training and mentoring, and online follow-up assistance. The matters discussed in this mentoring rest on the elaboration of critical evaluations from all coaching clinic teams on draft journal articles that have been made by participants. The service activity in the form of a Scientific Writing Clinic for Teachers Based on Participatory Action Research was followed carefully by the participants so that some participants were able to produce drafts of scientific papers that were worthy of publication in scientific journals, although of course various improvements were still needed to make them more perfect as articles. scientific. Keywords: Training and Mentoring, Scientific Writing, Teacher Kegiatan pelatihan menulis karya ilmiah untuk guru bertujuan untuk meningkatkan pola berpikir tumbuh (growth mindset) mengenai kecakapan menulis, memberikan paparan pada komponen-komponen penulisan dari ide mencari penelitian ke publikasi, meningkatkan kemampuan menulis karya ilmiah berbasis analisis kebutuhan participatory action research di kalangan guru dan stakeholders sekolah, para guru dapat mengembangkan self efficacy dan karirnya dengan menulis, serta menghasilkan draft artikel jurnal ilmiah bagi masing-masing peserta program pengabdian. Kegiatan Klinik Penulisan Ilmiah Bagi Para Guru Berbasis Participatory Action Research ini terdiri dari dua kegiatan utama, yaitu pelatihan dan pendampingan yang dilakukan secara offline, serta pendampingan lanjutan yang dilakukan secara online. Hal-hal yang dibahas pada pendampingan ini bertumpu pada penjabaran evaluasi kritis dari semua tim coaching clinic terhadap draft artikel jurnal yang telah dibuat oleh peserta. Kegiatan pengabdian berupa Klinik Penulisan Ilmiah Bagi Para Guru Berbasis Participatory Action Research ini diikuti oleh secara seksama oleh para peserta sehingga beberapa peserta mampu menghasilkan draft karya tulisa ilmiah yang layak untuk diterbitkan di jurnal ilmiah, meskipun tentunya masih diperlukan berbagai perbaikan agar lebih sempurna menjadi sebuah artikel ilmiah. Kata kunci: Pelatihan dan Pendampingan, Karya Ilmiah, Guru